2021
DOI: 10.1128/msphere.01220-20
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Heterochromatin Protein 1 Function in the Malaria Parasite Plasmodium falciparum Using a Conditional Domain Deletion and Swapping Approach

Abstract: The human malaria parasite Plasmodium falciparum encodes a single ortholog of heterochromatin protein 1 (PfHP1) that plays a crucial role in the epigenetic regulation of various survival-related processes. PfHP1 is essential for parasite proliferation and the heritable silencing of genes linked to antigenic variation, host cell invasion, and sexual conversion. Here, we employed CRISPR/Cas9-mediated genome editing combined with the DiCre/loxP system to investigate how the PfHP1 chromodomain (CD), hinge domain, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 85 publications
0
3
0
Order By: Relevance
“…Studies revealed that knockdown of HP1 resulted in activation of AP2-G, and led to gametocytogenesis. These proteins are responsible for the expression and repression of AP2-G considering the existing situation ( Coleman et al, 2014 ; Brancucci et al, 2014 ; Bui et al, 2021 ).…”
Section: Biology Of Plasmodium Gametocytementioning
confidence: 99%
“…Studies revealed that knockdown of HP1 resulted in activation of AP2-G, and led to gametocytogenesis. These proteins are responsible for the expression and repression of AP2-G considering the existing situation ( Coleman et al, 2014 ; Brancucci et al, 2014 ; Bui et al, 2021 ).…”
Section: Biology Of Plasmodium Gametocytementioning
confidence: 99%
“…In addition, they could be involved in heterochromatin formation at subtelomeric loci, through interaction with the major heterochromatic hallmarks of P . falciparum , H3K9me3, and PfHP1 [ 85 , 94 , 121 123 ]. Another possible similarity is the involvement of PfRad51 in telomere healing used by the parasites to repair double-stranded breaks within the subtelomeric regions [ 124 , 125 ].…”
Section: How Do Lncrnas Regulate Gene Expression?mentioning
confidence: 99%
“…falciparum is triggered by the master transcriptional regulator PfAP2-G ( Fig 2D ) [ 92 ]. In asexual blood-stage parasites, Pfap2-g is silenced by heterochromatin protein 1 (PfHP1) [ 93 , 94 ]. However, during sexual commitment, P .…”
Section: Introductionmentioning
confidence: 99%